'Bad character', tragic errors and deep ignorance. (December 2019) - Levanon, Liat
Abstract: This paper proposes new grounds for the legal ambivalence about 'bad character evidence'. It is suggested that errors based on such evidence are profoundly tragic in the Aristotelian sense: the defendant who previously committed crime is likely to reoffend; nevertheless, she beats the odds and refrains from further crime commission – only to then be falsely convicted based on the very odds she has almost heroically managed to beat. It is further proposed that the tragic nature of such false convictions might make them particularly unfair to the defendant. It is, however, submitted that the likelihood of errors based on such evidence is unknown and probably also unknowable. Accordingly, the maximin rule for decision in conditions of deep ignorance is applied, leading to the conclusion that exclusion is to be preferred.